Karpal Singh : Tiger of Jelutong - Donoghue, Tim (2013)
Karpal Singh is widely regarded as the best criminal and constitutional lawyer practising in Malaysia today. Since graduating from the University of Singapore in 1969 he has been a fearless, intelligent advocate for justice and a defender of human rights in South East Asia, and has appeared in the Privy Council in London on a number of occasions before such appeals were abandoned by Malaysia. In his long and illustrious career, Karpal Singh has defended more people headed for death row in Malaysian jails than he cares to remember. More importantly he has developed an international reputation f.